Characterization of the growth, productivity and physical fiber properties of indigenous cashmere goats in southern Kyrgyzstan - Toigonbaev, S.; Kerven, C.; Mueller, Joaquin Pablo; Khaliapov, T.; Abdikarimov, A.; McGregor, B.A. (Elsevier, 2023)
Since 2008, a breeding flock of Kyrgyz indigenous goats has been developed by a Kyrgyz non-government organisation (NGO) in the mountainous region of Osh Province in southern Kyrgyzstan, to preserve, select and distribute improved cashmere goats to villagers to increase their income from selling fine white cashmere. The NGO has trained farmers in 31 villages on better goat management and cashmere harvesting, established and advises 22 villages in a community-based breeding program with the foundation of improved sires and females from the NGO’s nucleus flock. This report provides the initial characterisation of the phenotypic, genetic and socio-economic value of this cashmere landrace. Live weights for females were (mean±s.d., kg): 1-year old, 27.4 ± 3.0 (n = 54); adult 6-years and older, 37.8 ± 4.8 (n = 58); and for males: 1-year old, 28.8 ± 3.2 (n = 40); 3-year old, 55–60 (n = 3). Using measurements (means±s.d.) taken on one-year old goats born between 2017 and 2021, shows cashmere weight (CW) 123 ± 56 g (n = 240), mean fiber diameter (MFD) 14.9 ± 1.2 µm (n = 332) and cashmere length (CL) 30.1 ± 6.7 mm (n = 200). Applying a linear animal model including birth year, birth type and sex we calculated heritabilities and their sampling errors (s.e.) as 0.12 ± 0.12, 0.58 ± 0.16 and 0.50 ± 0.24 for CW, MFD and CL, respectively. Genetic correlations between CW and both MFD and CL resulted rather low (−0.22 ± 0.54 and 0.16 ± 0.57) and between MFD and CL rather high (0.48 ± 0.25). Similarly, phenotypic correlations between CW and both MFD and CL resulted low (0.12 ± 0.07 and 0.22 ± 0.09) and between MFD and CL high (0.49 ± 0.06). Cashmere weight has increased 2.6 g per year (P = 0.017) while cashmere MFD has not decreased significantly (P = 0.066). There has also been no significant increase in cashmere length (P > 0.3). Changes in the average selection index since 2019 indicated additional economic worth of 10% (P = 0.017). Various body dimensional characteristics were measured. Heart girth measurement accounted for 80% of the variance in live weight indicating girth would be a useful field measurement method in remote regions. Given the positive phenotypic correlation between cashmere production and MFD continuing objective measurement of cashmere production and MFD are essential for future improvements in economic benefits for farmers.